Formulation of Fermented Earthworm (Lumbricus rubellus) Lotion as a Therapy for Atopic Dermatitis - Irianto, Iramie Duma Kencana; Kurniadi, Muslih; Ismiyati, Ismiyati; Trilestari, Trilestari (Tropical Biopharmaca Research Center, IPB University, 2025)
The prevalence of atopic dermatitis in industrialised countries has increased two- to threefold over the past 30 years. Fermented earthworm (Lumbricus rubellus) extract has been shown to effectively reduce atopic dermatitis by increasing interleukin-10 (IL-10) and FOXP3, and decreasing interleukin-5 (IL-5), interleukin-31 (IL-31), immunoglobulin E (IgE), and eosinophils. The extract has also been reported to inhibit the growth of skin surface bacteria, particularly Streptococcus aureus, at a minimum inhibitory concentration (MIC) of 0.625%. L. rubellus contains lumbricin-I, proline-rich antimicrobial peptides (AMPs), lumbrokinase, lysenin, and coelomic cytolytic factor-1 (CCF-1), which play important roles in anti-inflammatory and antibacterial responses. Cetyl alcohol influences the viscosity of semi-solid preparations, thereby affecting the lotion's quality and stability. This study aimed to determine the optimum concentration of cetyl alcohol in the formulation of fermented L. rubellus lotion with good physical characteristics. The lotion was formulated by varying the concentration of cetyl alcohol and comparing it with commercial lotion based on organoleptic properties, pH, adhesion, spreadability, and physical stability using a cycling test. Lotion formulas F2 (0.5% cetyl alcohol) and F3 (1% cetyl alcohol) exhibited physical properties similar to the positive control, remained semi-solid, and were comfortable to use. A 1% concentration of cetyl alcohol was found to be optimal for maintaining pH stability and spreadability of the fermented L. rubellus lotion.